#Peyronies: An Analysis of Online Twitter Discussion of Peyronie's Disease. Issue 1 (January 2020) - Balasubramanian, Adithya; Yu, Justin; Lipshultz, Larry I.; Hotaling, James M.; Pastuszak, Alexander W.
Abstract: Introduction: We quantitatively and qualitatively analyzed Twitter Peyronie's disease discussions using the hashtag #Peyronies. Methods: Symplur, a Twitter analytics service, was used to analyze Twitter activity, users and content for #Peyronies, the official hashtag for Peyronie's disease, between April 2013 and September 2018. Activity was measured by tweets per month and cumulative users per year. Users were classified based on geography, occupation and organizational affiliation. Content analysis was performed by retrieving information about Twitter engagement metrics including retweets, links, media, mentions, replies, frequently used words and hashtags. Results: A total of 3, 278 tweets and 767 users employing #Peyronies were identified. Most tweets (75%) were sent with links and contained media images (49%). The average ± SD number of #Peyronies tweets per month increased from 17.7 ± 8.5 in 2013 to 121.4 ± 52.2 in 2018 (p <0.001). The number of users increased from 77 to 767 during this period and users tweeted from 61 countries. Physicians comprised 46% of the top influencers. Common words in #Peyronies tweets were "disease, " "men" and "andropeyronie." Popular associated hashtags were #menshealth, #peyronie and #men. Codification of tweet content revealed that tweets were focused on clinical care discussions or online patient support. Conclusions: Our analysis demonstrates that Peyronie's disease Twitter discussions are growing. Although discussion volume is smaller relative to other benign urological pathologies such as kidney stones, this study shows that Peyronie's disease discussions are present on Twitter and are attracting users. Twitter is a digital tool that influences awareness and perceptions of Peyronie's disease.